2021
DOI: 10.1080/14659891.2021.1961890
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use in English adolescent students–result of cumulative mediation analyses

Abstract: Background: In England, drug use in young people increased significantly between 2014 and 2017. This upward trend continues despite implementation of drug use policies to reduce supply, possession and manufacture of illicit drugs. Taking the view that drug use is a learnt behaviour, the purpose of this paper is to evaluate whether social learning (SL) factors explain drug use in English adolescents across: a) nine regions b) by age (11 to 15 years) and c) by gender using the Social Structure Social Learning (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…We found that both past-year and current illicit drug use among ABYM increased with increasing age. Our findings are consistent with findings from the United States which found an increase in use of any tobacco products and marijuana with age [ 38 , 44 ], and resonate with findings from England which reported a similar pattern [ 45 ]. Altogether, these studies confirm that age is a key influencer for illicit drug use, especially among older adolescents and young men.…”
Section: Discussionsupporting
confidence: 92%
“…We found that both past-year and current illicit drug use among ABYM increased with increasing age. Our findings are consistent with findings from the United States which found an increase in use of any tobacco products and marijuana with age [ 38 , 44 ], and resonate with findings from England which reported a similar pattern [ 45 ]. Altogether, these studies confirm that age is a key influencer for illicit drug use, especially among older adolescents and young men.…”
Section: Discussionsupporting
confidence: 92%
“…Threats related to darknet web services have been reported by many authors [12]. At the same time, it is interesting to note that, for example, English teenagers and college students tried a drug for the first time in the company of their peers or older friends, which means that there were imitative, playing and group motives dominating with them [13]. All these features of drug addicted teenagers were clearly confirmed by the results of our study.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research is also inconsistent regarding the association between gender and substance use. Some research suggests that gender does not predict use of tobacco and alcohol ( Van Ryzin et al, 2012 ) or illegal substances ( Van Ryzin et al, 2012 ; Wilkhu, 2021 ). Other studies indicate that males and females may be affected differently by specific domains during specific periods of their lives ( Epstein et al, 2017 ).…”
Section: The Public Health Model For Prevention Of Disease and Disordermentioning
confidence: 99%